Implementing a Sleep Health Education and Sleep Disorders Screening Program in Fire Departments: A Comparison of Methodology. Issue 6 (June 2016) - Barger, Laura K.; O'Brien, Conor S.; Rajaratnam, Shantha M.W.; Qadri, Salim; Sullivan, Jason P.; Wang, Wei; Czeisler, Charles A.; Lockley, Steven W.
Abstract : Objective: The objective of this study is to compare three methods of administering a sleep health program (SHP) in fire departments. Methods: An SHP, comprising sleep health education and screening for common sleep disorders, was implemented in eight fire departments using three approaches: expert-led, train-the-trainer, and online. Participation rates, knowledge assessments, surveys, and focus group interviews were analyzed to assess the reach and effectiveness of the methodologies. Results: The Expert-led SHP had the highest participation rate, greatest improvement in knowledge scores, and prompted more firefighters to seek clinical sleep disorder evaluations (41%) than the other approaches (20 to 25%). Forty-two percent of focus group participants reported changing their sleep behaviors. Conclusion: All approaches yielded reasonable participation rates, but expert-led programs had the greatest reach and effectiveness in educating and screening firefighters for sleep disorders.